2018
DOI: 10.1108/bfj-01-2018-0030
|View full text |Cite
|
Sign up to set email alerts
|

Promoting value addition among farmers in the cassava food value chain in Nigeria

Abstract: Purpose The purpose of this paper is to analyse the effects of the determinants of farmer participation in value addition through cassava processing in Nigeria. Design/methodology/approach This study employs the probit model to analyse the determinants of farmer participation in value addition whereas the Tobit model is used to investigate the determinants of the extent of producer’s involvement in value addition using a data set of 400 cassava farmers drawn from the Oyo State of Nigeria. Findings The find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 17 publications
6
19
1
Order By: Relevance
“…This result concurs with the finding by Alkan and Kumar, (2018) that storage was one of the best strategies for mango value addition and post-harvest management practice among small-scale farmers. This finding contradicts results by Donkor et al (2018) that lack of storage facilities reduces the active participation of farmers to value addition along the local value chain.…”
Section: Determinants Of Farm-level Value Addition Among Small-scale contrasting
confidence: 86%
See 1 more Smart Citation
“…This result concurs with the finding by Alkan and Kumar, (2018) that storage was one of the best strategies for mango value addition and post-harvest management practice among small-scale farmers. This finding contradicts results by Donkor et al (2018) that lack of storage facilities reduces the active participation of farmers to value addition along the local value chain.…”
Section: Determinants Of Farm-level Value Addition Among Small-scale contrasting
confidence: 86%
“…Value addition is achieved through innovation and coordination processes (Donkor, Onakuse, Bogue, and de los Rios Carmenado, 2018) . However, Farmers' interest to add value to their product through innovation and coordination is largely limited by the market environment, supportive services, processing technologies, infrastructure, institutional, economic, and socio-demographic factors (Gashaw, Habteyesus, and Nedjo, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies on the CVC focus on the production node, with only a few studies considering activities at the processing and market nodes of the chain. At the production node, studies address issues related to adoption of improved cassava varieties (Opata et al, 2021;Afolami et al, 2015;Wossen et al, 2018), choices of marketing channels (Donkor et al, 2018a), value addition (Donkor et al, 2018b) and profitability of cassava production (Obayelu et al, 2013;Omotayo and Oladejo, 2017;Ojiako et al, 2018;Donkor et al, 2019;Rahman and Chima, 2016). Afolami et al (2015) found that the adoption of improved cassava varieties increased the annual income and consumption expenditure of farming households in southwestern Nigeria.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The factors determining a baobab collector's choice of marketing channel are grouped into human capital, transactional and institutional factors. This categorisation is based on Donkor et al's (2018a) study on promoting value addition among cassava farmers in Nigeria. Variables categorised under human capital include the collector's gender, age, number of children, marital status, other incomes, number of baobab trees, baobab collection point, experience of selling baobab and number of known buyers.…”
Section: Hypothetical Determinants Of Marketing Channelsmentioning
confidence: 99%